Effect of training on improving swimming biological age and capabilities of people aged 30-35 years - N.V. Fedinyak (H.S. Skovoroda Kharkov National Pedagogical University, 2014)
Purpose: to verify the anti-aging effect of improving navigation on involution processes of the human body 30-35. Material: participation in the experiment took 43 men and women aged 30-35 years. Biological age is measured by the method of V.P. Voytenko. Results: obtained reliably between biological age men engaged in wellness swimming and those who engage in other forms of physical activity. We found that swimming as non-drug product may be recommended to address the problem of premature aging. It is confirmed that the rate of aging men set the pace of aging women may be caused as a social (especially labor , bad habits, etc.) and sex specific (men still developing atherosclerosis, blood circulation of the brain). Conclusions: navigation as non-drug remedy is recommended to prevent premature aging .